Bromatological chemical evaluation of three varieties of Arracacia xanthorrhiza “arracacha” - Palacios, Rocío (2011)
Were evaluated the varieties yellow, white and purple of the species Arracacia xanthorrhiza “Arracacha”, , coming from Socota district of Cutervo province in department of Cajamarca, supplied for the “Instituto Nacional de Investigación Agraria” (INIA). Also are well-known like r’acacha, laqachu, rakkacha, virracacha, ricacha, arracacha, racacha, arrecate, zanahoria blanca, apio criollo, sonarca, virraca, zanahoria del país, zanahoria morada. They are consumed in greater percentage like fresh product and their stems to tier to us are used in salads or like vegetables cooked or mixed with other roots. They presents content of water of 71,34 to 73,86 grams percent. In dry sample: total protein 2,10 to 2,65; ash 2,26 to 2,81; ethereal extract 0,91 to 0,98; raw fiber 3,25 to 3,38; carbohydrates from 86,67 to 86,91; total reducing sugars 2,65 to 3,94 and caloric value of 363,40 to 365,78 grams percents. Vitamin C of 75,75 to 100,34 milligrams percent. Also they presents, in dry sample: calcium from 116,31 to 125,36; iron from 30,26 to 41,73; phosphorus from 175,98 to 215,78; potassium from 8,37 to 8,91; 261,43 magnesium from 214,12 to and zinc of 19,40 to 20,87 milligrams percent.